2007 IEEE 9th Workshop on Multimedia Signal Processing 2007
DOI: 10.1109/mmsp.2007.4412899
|View full text |Cite
|
Sign up to set email alerts
|

Image Authentication and Tampering Localization using Distributed Source Coding

Abstract: Abstract-Media authentication is important in content delivery via untrusted intermediaries, such as peer-to-peer (P2P) file sharing. Many differently encoded versions of a media file might exist. Our previous work applied distributed source coding to distinguish the legitimate diversity of encoded images from tampering. An authentication decoder was supplied with a Slepian-Wolf encoded lossy version of the image as authentication data. Distributed source coding provided the desired robustness against legitima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…Moreover, it is presently more and more accepted that the Distributed Source Coding (DSC) principles, notably the SlepianWolf and Wyner-Ziv theorems, are inspiring a varied set of tools which may help to solve different problems, not only coding, but also e.g. authentication and secure biometrics [26,27]. While it is difficult to state, at this stage, if any video coding product will ever use DSC principles, and in which way, it is most interesting to study and research towards this possibility.…”
Section: The Trendsmentioning
confidence: 99%
“…Moreover, it is presently more and more accepted that the Distributed Source Coding (DSC) principles, notably the SlepianWolf and Wyner-Ziv theorems, are inspiring a varied set of tools which may help to solve different problems, not only coding, but also e.g. authentication and secure biometrics [26,27]. While it is difficult to state, at this stage, if any video coding product will ever use DSC principles, and in which way, it is most interesting to study and research towards this possibility.…”
Section: The Trendsmentioning
confidence: 99%
“…Error locating coding, with channel codes also used for SW coding, was proposed in [13], [14]. A LDPC code was applied to detect (in a watermarking scenario) the location of the introduced tampering.…”
Section: B Error Locating Codingmentioning
confidence: 99%
“…Intermediaries might also tamper with the media for a variety of reasons, such as interfering with the distribution of a particular file, piggybacking unauthentic content, or generally discrediting a distribution system. In previous work, we applied distributed source coding (DSC) to image authentication to distinguish the diversity of legitimate encodings from malicious manipulation [1] and demonstrated that the same framework can localize tampering in images deemed to be inauthentic [2]. In this paper, we extend our image authentication scheme to be robust to affine warping.…”
Section: Introductionmentioning
confidence: 98%